2023
DOI: 10.1101/2023.09.17.558166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three new species,Xanthomonas hawaiiensissp. nov.,Stenotrophomonas aracearumsp. nov., andStenotrophomonas oahuensissp. nov., isolated from Araceae family

Shu-Cheng Chuang,
Shefali Dobhal,
Anne M. Alvarez
et al.

Abstract: Xanthomonas and Stenotrophomonas are closely related genera in the family Lysobacteraceae. In our previous study of aroid-associated bacterial strains, most strains isolated from anthurium, and other aroids were reclassified as X. phaseoli and other Xanthomonas species. However, two strains from Spathiphyllum and Colocasia were phylogenetically distant from other strains in the Xanthomonas clade and two anthurium strains clustered within the Stenotrophomonas clade. Phylogenetic trees based on 16S rRNA and nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…nov. (A2111), X. citri pv. aracearum (A6252), X. sacchari (A5592), and X. sontii (A6237) 26 . Two control groups were included: one with healthy sugarcane and another with a non-template control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…nov. (A2111), X. citri pv. aracearum (A6252), X. sacchari (A5592), and X. sontii (A6237) 26 . Two control groups were included: one with healthy sugarcane and another with a non-template control.…”
Section: Resultsmentioning
confidence: 99%
“…nov. (A2111), X. citri pv. aracearum (A6252), X. sacchari (A5592), and X. sontii (A6237) 26 . The plates were incubated for 2 days at 28 °C.…”
Section: Methodsmentioning
confidence: 99%
“…However, the close relationship between X. sacchari, X. sontii, X. indica and a recently reported species, X. hawaiiensis, that form a clade, it is important to use the right and multiple approaches even when using genomic information to establish the species identity [43]. This is because, in literature, even the genome-based focussed studies have wrongly reported X. sontii strain(s) as X. sacchari [44,45].…”
Section: Frequent Misclassification Of X Sontii Isolates As X Saccharimentioning
confidence: 99%
“…With the new possibilities of complete 16S rRNA sequence metagenomic studies using long-read sequencing technologies and the advent of deep metagenomics and the genomic era can provide much-required resolution and confidence in diversity and culturomics studies. However, the close relationship between X. sacchari, X. sontii, X. indica and a recently reported species, X. hawaiiensis , that form a clade, it is important to use the right and multiple approaches even when using genomic information to establish the species identity [43]. This is because, in literature, even the genome-based focussed studies have wrongly reported X. sontii strain(s) as X. sacchari [44, 45].…”
Section: Introductionmentioning
confidence: 99%